2018
DOI: 10.1007/s40519-018-0530-1
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning and psychological symptoms in food addiction: a study among individuals with severe obesity

Abstract: Food addiction (FA) has recently emerged as a new field in the study of obesity. Previous studies have contributed to identifying psychological correlates of FA. However, few researchers have examined the cognitive profile related to this condition; up until now, attentional biases related to food cues and a poorer performance monitoring have been observed. The present study aimed to examine the psychological profile and executive functioning related to FA in individuals with severe obesity and awaiting bariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Specifically, some studies found no evidence of impaired performance (Chamberlain et al, 2015; Fagundo et al, 2016; Manasse et al, 2014; Schiff et al, 2016; Wu et al, 2016), while other studies found impaired set-shifting in participants with overweight or obesity relative to healthy controls (Gameiro et al, 2017; Steenbergen and Colzato, 2017) and eating disorder patients (Perpiñá et al, 2017). Studies have also shown impaired set-shifting in obese participants with BED, but not in those without (Banca et al, 2016), and obese participants with high, but not low FA symptoms (Rodrigue et al, 2018).…”
Section: Review Of Findingsmentioning
confidence: 98%
“…Specifically, some studies found no evidence of impaired performance (Chamberlain et al, 2015; Fagundo et al, 2016; Manasse et al, 2014; Schiff et al, 2016; Wu et al, 2016), while other studies found impaired set-shifting in participants with overweight or obesity relative to healthy controls (Gameiro et al, 2017; Steenbergen and Colzato, 2017) and eating disorder patients (Perpiñá et al, 2017). Studies have also shown impaired set-shifting in obese participants with BED, but not in those without (Banca et al, 2016), and obese participants with high, but not low FA symptoms (Rodrigue et al, 2018).…”
Section: Review Of Findingsmentioning
confidence: 98%
“…The diagnosis of BED according to DSM-5 [25] was derived from the diagnostic items of the validated German version of the Eating Disorder Examination interview (EDE 17.0D) [44,45]. According to DSM-5, the following severity levels of BED were determined: mild (1–3 objective binge-eating episodes per week), moderate (4–7 objective binge-eating episodes per week), severe (8–13 objective binge-eating episodes per week), and extreme (≥14 objective binge-eating episodes per week).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the clinical eating disorder diagnosis of binge-eating disorder (BED) [25] has been associated with addictive-like eating behavior [26,27]. According to the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [25], the core feature of BED is represented by recurrent episodes of objective binge eating, which are characterized by a feeling of loss of control over eating while consuming an unambiguously large amount of food in a discrete period of time. BED is not associated with regular inappropriate compensatory behaviors, such as vomiting or excessive exercising [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigue et al [59] compared those with higher and lower food addiction scores on cognitive processes of planning, inhibition, cognitive flexibility and error processing. The investigators found that high food addiction group differed from the low food addiction group only in terms of inhibition/cognitive flexibility scaled scores, but not in individual scores.…”
Section: Psychological Correlates Of Addiction To Fat Rich Dietsmentioning
confidence: 99%